2020
DOI: 10.2147/copd.s242009
|View full text |Cite
|
Sign up to set email alerts
|

<p>Management of the COPD Patient with Comorbidities: An Experts Recommendation Document</p>

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is associated with multiple comorbidities, which impact negatively on patients and are often underdiagnosed, thus lacking a proper management due to the absence of clear guidelines. Purpose: To elaborate expert recommendations aimed to help healthcare professionals to provide the right care for treating COPD patients with comorbidities. Methods: A modified RAND-UCLA appropriateness method consisting of nominal groups to draw up consensus recommendations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 301 publications
(352 reference statements)
0
29
0
4
Order By: Relevance
“…However, not all the mechanisms for the development and advance of this pathology have been fully understood. The development of chronic systemic inflammation is found to be the characteristic of COPD and the appearance of systemic effects [ 11 ], leading to an increased incidence of concomitant pathology [ 12 , 13 ]. The incidence of type 2 diabetes mellitus (DM) with COPD is proved to be higher than in the case of its absence [ 14 - 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, not all the mechanisms for the development and advance of this pathology have been fully understood. The development of chronic systemic inflammation is found to be the characteristic of COPD and the appearance of systemic effects [ 11 ], leading to an increased incidence of concomitant pathology [ 12 , 13 ]. The incidence of type 2 diabetes mellitus (DM) with COPD is proved to be higher than in the case of its absence [ 14 - 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Существующие рекомендации по ведению и лечению пациентов с ХОБЛ свидетельствуют о том, что «лечение СН у пациентов с ХОБЛ должно проводиться в соответствии со стандартными рекомендациями, поскольку нет данных о том, что СН следует лечить иначе при наличии ХОБЛ» [2,6]. Таким образом, при определении тактики лечения ХСН у больных ХОБЛ необходимо ориентироваться на Национальные рекомендации ОССН, РКО и РНМОТ по диагностике и лечению ХСН [7], а также на рекомендации Российского общества терапевтов по лечению пациентов с ХСН и ХОБЛ [8].…”
Section: Discussionunclassified
“…Особенностью современного пациента является полиморбидность, которая в значительной мере изменяет клиническое течение, прогноз основного заболевания и вносит коррективы в тактику лечения. Наиболее частыми причинами одышки у пожилых больных являются хроническая обструктивная болезнь легких (ХОБЛ) и хроническая сердечная недостаточность (ХСН) [1][2][3][4]. Распространённость сердечной недостаточности колеблется от 5% до 60% в общей популяции ХОБЛ и увеличивается в соответствии с тяжестью ХОБЛ, составляя приблизительно 30% у пациентов, госпитализированных с обострением ХОБЛ и 75% у пациентов, перенёсших искусственную вентиляцию легких [1][2][3][4].…”
Section: Introductionunclassified
“…A meta-analysis of 37 studies by Singanayagam et al ( 33 ) reported that low body mass index, cardiac failure, diabetes mellitus, ischemic heart disease and malignancy are significantly associated with increased mortality in patients with acute exacerbations of COPD. It is also reported that the presence of more than one co-morbidity may double the risk of COPD-associated mortality ( 34 ). Furthermore, similar co-morbidities are known to also influence outcomes of VAP ( 18 ).…”
Section: Discussionmentioning
confidence: 99%